The Abilities in Applying Verb Tenses in Writing Sentence Using Mixed Model - Herdi Herdi (Universitas Lancang Kuning, 2014)
This research intends to identify the students’ ability and the common problems in mastering verb tenses in writing sentences. The research tries to identify students’ ability in applying verb tenses in their writing and to explain the problems found in using verb tense in their writing. This research used mixed methods. The participants of the research were the second year students of English Department FKIP UNILAK Pekanbaru. The findings showed the students’ ability categorized “less”. The data also reveals that the students’ common problems in mastering verb tenses in writing sentence was classified in two groups; they were the students’ common problems with verb tenses such as errors in time expresses, duration of the action, and aspect of the action beyond its time and the problems influencing the students’ ability in applying verb tenses in writing sentences such as lack of work on exercises, lazy to review the lesson, and do not have enough time to study verb tenses in the class.